Gene expression and DNA methylation during in vitro culture and plant regeneration in Boesenbergia rotunda (L.) Mansf / Md. Rezaul Karim - Md. Rezaul , Karim (2017)
In vitro culture and plant regeneration via somatic embryogenesis are important for crop improvement. These processes involve changes in gene expression and are also associated with changes in DNA methylation. Therefore, it is of interest to determine the changes in gene expression and in DNA methylation during in vitro culture and plant regeneration. Boesenbergia rotunda, an important medicinal plant in South-East Asia, India and Southern China, was chosen as a model system for this study in which the expression patterns of three DNA methylation pathway genes, METHYLTRANSFERASE 1 (MET1), CHROMOMETHYLASE 3 (CMT3) and DOMAIN REARRANGED METHYLTRANSFERASE 2 (DRM2), and four somatic embryogenesis related genes, SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK), BABY BOOM (BBM), LEAFY COTYLEDON 2 (LEC2) and WUSCHEL (WUS) were examined using qRT-PCR and RNA-seq in various cell samples, representing different stages of the regeneration process, from explant through somatic embryogenesis and regeneration. DNA methylation patterns and levels were determined by Methylation Sensitive Amplified Polymorphism (MSAP) and Bisulfite sequencing (BS-seq). Gene and amino acid sequences of MET1, CMT3, DRM2, SERK, BBM, LEC2 and WUS from B. rotunda showed high similarity and conserved domains with genes of the same function from other plants in the Genbank database. Phylogenetic analysis indicated that B. rotunda deduced protein sequences were evolutionarily most related to those from Musa acuminata. There was higher expression of methyltransferase genes MET1, CMT3 and DRM2, and hypomethylation in embryogenic calli, which may be associated with successful somatic embryogenesis and regeneration. Expression of genes related to somatic embryogenesis and regeneration, SERK, BBM, LEC2 and WUS, was higher in embryogenic callus and lower in non-embryogenic calli and twelve-month old suspension cells. Lower levels of DNA methylation at the loci of SERK, BBM, LEC2 and WUS in terms of CG, CHG and CHH methylation were associated with the higher expression of those genes, thus this may promote embryogenic competence during in vitro culture of B. rotunda. Pearson’s Correlation analyses showed that higher DNA methylation of the MET1, CMT3, DRM2, SERK, BBM, LEC2 and WUS loci was mostly negatively correlated with the expression of those genes, especially for in vitro calli and cell suspension culture. These findings in this study may form a foundation for future research to optimize genetic and epigenetic control of plant somatic embryogenesis and regeneration during in vitro culture.